STATUS KEBERADAAN EKONOMI KREATIF MASYARAKAT PESISIR DI KECAMA-TAN KEMA KABUPATEN MINAHASA UTARA (Status of the Creative Economic Existence of Coastal Communities in Kema Sub-District, Minahasa Utara Regency) - Nathalia Novita Sumampou; Melsje J. Memah; Lyndon Pangemanan (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
This study aims to determine and describe the status of the creative economic existence of coastal communities in Kema District, North Minahasa Regency. This research was conducted from May to November 2021. The data used in this study were primary data and secondary data. The method used in this research was descriptive qualitative analysis method. A gradual sampling method was applied, namely the purposive sampling method and the simple random sampling method, in choosing 20 respondents. Existence status was a situation or condition, which in this study was an ongoing creative economic activity in coastal communities seen from motivation, creativity and innovation, financial management, environment, and government.